Short- and medium-term cost effects of non-indicated thyroid diagnostics: empirical evidence from German claims data - Lucas Hafner; Valeria Biermann; Susann Hueber; Ewan Donnachie; Thomas Kühlein; Harald Tauchmann; Johanna Tomandl (The European Journal of Health Economics, 2021)
This paper contributes to the discussion of whether non-indicated ultrasound examinations of the thyroid gland contribute to overtreatment and excess health care expenditures. Using two sources of claims data from Germany, we analyzed data from patients who underwent a TSH blood test which is the initial diagnostic measure to check for possible presence of thyroid dysfunction. In a matching analysis, we compared health costs of two groups of patients. One consisted of patients who underwent an early thyroid ultrasound that according to medical guidelines—at this point—was probably not indicated. The other group consisted of patients, who underwent no ultrasound examination at all or later in the course of the disease, making probable a correct indication. Both groups were made comparable by the means of a matching procedure. Average thyroid-specific health costs were substantially higher for the first group in the quarter in which the ultrasound examination took place. Some deviation in these specific costs persisted over a substantial period of time, with drug expenditures exhibiting the biggest difference. If, however, total health costs were considered, difference in costs was only found in the initial quarter. We conclude that non-indicated ultrasound examination of the thyroid gland may have some moderate effects on thyroid-specific costs. Yet the data do not suggest that long-lasting overtreatment and excess health expenditures are initiated by non-indicated ultrasound in Germany.
Keywords: I11; I18; 610; Matching; Health cost; Non-indicated ultrasound; Thyroid anomalies